2008
DOI: 10.1074/jbc.m709657200
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide Analysis Identifies Interleukin-10 mRNA as Target of Tristetraprolin

Abstract: Tristetraprolin (TTP) is an RNA-binding protein required for the rapid degradation of mRNAs containing AU-rich elements. Targets regulated by TTP include the mRNAs encoding tumor necrosis factor-␣, granulocyte-macrophage colony-stimulating factor, interleukin-2 (IL-2), and immediate early response 3. To identify novel target mRNAs of TTP in macrophages, we used a genome-wide approach that combines RNA immunoprecipitation and microarray analysis. A list was compiled of 137 mRNAs that are associated with TTP wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
199
2
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 217 publications
(211 citation statements)
references
References 51 publications
8
199
2
2
Order By: Relevance
“…It was shown recently that bone marrow-derived macrophages from TTP-deficient mice have longer IL-10 mRNA t 1/2 than the cells from wild-type mice, indicating that IL-10 can be regulated by TTP in a posttranscriptional manner (16). It is possible that miR-466l upregulates IL-10 expression by downregulating TTP.…”
Section: Upregulation Of Il-10 Production By Mir-466l Most Likely Occmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown recently that bone marrow-derived macrophages from TTP-deficient mice have longer IL-10 mRNA t 1/2 than the cells from wild-type mice, indicating that IL-10 can be regulated by TTP in a posttranscriptional manner (16). It is possible that miR-466l upregulates IL-10 expression by downregulating TTP.…”
Section: Upregulation Of Il-10 Production By Mir-466l Most Likely Occmentioning
confidence: 99%
“…TTP coordinately destabilizes these transcripts by recruiting the RNA decay machinery (15). TTP also can destabilize the anti-inflammatory cytokine IL-10 mRNA by binding to the ARE (16). It has been concluded that miRNAs mediate target mRNA degradation or translation repression modestly (17), whereas RBPs, such as TTP, can mediate rapid mRNA degradation (18,19).…”
mentioning
confidence: 99%
“…TTP belongs to a family of evolutionary conserved zinc finger RNA-binding proteins able to bind AREs, thereby accelerating mRNA degradation. First identified as a regulator of TNF-␣ production (2), TTP has since been recognized to control the degradation of a large variety of ARE mRNAs including mediators of the inflammatory and the anti-inflammatory responses (3,4). The TIS11 protein family contains three members in humans and four members in mice.…”
mentioning
confidence: 99%
“…Previously, we also confirmed with two different reporter genes, luciferase and EGFP, that the 39 UTR of IL-10 negatively regulates the protein production (19). The rapid degradation of Il10 mRNA is mediated, for example, by binding of AU-rich element binding factor 1, tristetraprolin, or microRNA (hsamiR-106a) to the 39 UTR (40,43,44). Taken together, this intrinsic instability of Il10 mRNA results in low and transient expression of IL-10 protein and consequently restricts the sensitivity of a reporter gene like EGFP that is known to have a high limit of detection (∼10 5 molecules/cell) (7).…”
Section: Discussionmentioning
confidence: 61%